Persistent radiographic cone cuts: A simple test to avoid the frustrating problem - Santosh Gowdru Shivanandappa; Lata Shankarappa Mushannavar; Girish Katti (Wolters Kluwer Medknow Publications, 2014)
In routine dental radiography, one may encounter numerous radiographic errors, one of which may be partial images or cone cuts. These cones cut errors although may appear as simple problems, but often persistent cone cuts may be frustrating to the dental practitioner. In this study, our main aim was to find and solve the origin of the problem. This study was conducted with two different intraoral X-ray machines with 12 inch length position indicating devices (PIDs) with four No. 2 intraoral films. If the problem is originated in the X-ray machine, it can be solved by either tapping the collimator or by repositioning the PID.